PKM (Pengabdian Kepada Masyarakat) Pentingnya Nilai-nilai Budaya Yang Terkandung dalam Cerita Rakyat Putri Runduk Sibolga Di Kelurahan Pintu Padang,Kecamatan Batang Angkola,Kabupaten Tapanuli Selatan, Sumatera Utara - Juliana Siregar; Olivia Feby Mon Harahap (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Folklore is an example of a culture that exists today and must be preserved because most people today hardly even remember what folklore is. Because folklore comes from the community, that community should also preserve cultural heritage, namely folklore. Based on the background of the research, the researcher will focus on analyzing the Cultural Values ​​in the folklore of Putri Runduk Sibolga because culture is closely related to our lives as for the cultural values ​​that are focused on. namely cultural values ​​in human relations with religiosity, cultural values ​​in human relations with humans, cultural values ​​from human relationships with nature. Based on the description above, the researcher wants to examine more deeply the cultural values ​​contained in the folklore of Putri Runduk Sibolga.